2022
DOI: 10.1136/bmjqs-2021-014329
|View full text |Cite
|
Sign up to set email alerts
|

Quality framework for remote antenatal care: qualitative study with women, healthcare professionals and system-level stakeholders

Abstract: BackgroundHigh-quality antenatal care is important for ensuring optimal birth outcomes and reducing risks of maternal and fetal mortality and morbidity. The COVID-19 pandemic disrupted the usual provision of antenatal care, with much care shifting to remote forms of provision. We aimed to characterise what quality would look like for remote antenatal care from the perspectives of those who use, provide and organise it.MethodsThis UK-wide study involved interviews and an online survey inviting free-text respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 54 publications
1
39
0
3
Order By: Relevance
“…Trust exibility and proactivity allowed enhanced care to remain in place for women with high-risk pregnancies or who are from vulnerable backgrounds, and women who needed interpreters were still seen face to face. This demonstrates that staff were reacting to concerns that remote consultations can lead to inequitable care, a nding also established in other recent research (25,29). Staff reported that, in their Trusts, women from ethnic minorities were more likely to fall into these vulnerable groups.…”
Section: Strengths and Limitationssupporting
confidence: 69%
“…Trust exibility and proactivity allowed enhanced care to remain in place for women with high-risk pregnancies or who are from vulnerable backgrounds, and women who needed interpreters were still seen face to face. This demonstrates that staff were reacting to concerns that remote consultations can lead to inequitable care, a nding also established in other recent research (25,29). Staff reported that, in their Trusts, women from ethnic minorities were more likely to fall into these vulnerable groups.…”
Section: Strengths and Limitationssupporting
confidence: 69%
“…Three interviews were conducted during the COVID-19 pandemic. The rapid change to the provision of remote antenatal care, compelled women to adjust to new ways of accessing and receiving antenatal care and information [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun OR-nya tampak tinggi, hanya dua penelitian yang melaporkan hasil ini, sehingga jumlahnya kecil. Mereka juga melaporkan bahwa wanita tidak mengalami peningkatan risiko kelahiran instrumental (OR 1,44 [95% CI 0,95, 2,18], p = 0,09; N = 1020) atau episiotomi (OR 1,04 [95% CI 0,20], p = 0,93; N = 244) (Güneş Öztürk, Akyıldız and Karaçam, 2022). Duryea dkk.…”
Section: Intervensi Kelahiranunclassified
“…Tidak menunjukkan perbedaan antara telehealth dan perawatan konvensional untuk komplikasi neonatal. Ini termasuk skor Apgar 5 menit yang rendah <7 (OR 0,54 [95% CI 0,14, 2,14], p = 0,38; N = 236], sindrom gangguan pernapasan (OR 0,65 [95% CI 0,38,1,13], p = 0,99; N = 928), hipoglikemia (OR 1.18 [95% CI 0.74,1.87], p = 0.48; n = 701), dan hiperbilirubinemia (OR 0.86 [95% CI 0.48, 1.54], p = 0.61; N = 583) (Güneş Öztürk, Akyıldız and Karaçam, 2022). Penelitian lain mendukung temuan ini, selain tidak adanya peningkatan risiko asfiksia neonatal atau pH tali pusat yang rendah.…”
Section: Hasil Neonatalunclassified